Personalised Medicine : A Critical Approach to Data-Driven Medicine - Michael Morrison; Saheli Datta Burton (Routledge, 2026)
This book sets out a critical sociological approach to ‘personalised medicine'(PM), not only highlighting its limitations and flaws but also emphasising its hopeful potentialities for a better medicine in the future.Bringing together perspectives from science and technology studies, medical sociology, law, and bioethics, this book traces PM from its historical roots in disease classification and predictive genetics to its data-driven present of digital infrastructures, algorithmic prediction, and precision therapeutics. Across seven chapters, it explores how measurement, classification, and datafication shape medical knowledge; how infrastructures and platforms distribute benefits and risks; how publics are imagined as patients, consumers, and citizens; and how privacy, access, and equity are negotiated in global health systems. This book concludes by outlining possible futures grounded in solidarity, patient-centred care, and democratic innovation – offering practical ways to shift PM from a privilege for the few to a shared public good.Written for scholars and practitioners in science and technology studies, sociology of medicine, health policy, and bioethics, as well as for clinicians and policymakers, this book will engage readers seeking to understand – and reshape – the social futures of data-intensive healthcare. It will also be useful for policy makers debating the implementation of different PM projects in local or national healthcare systems.